Attention Utility: Evidence from Individual Investors - Quispe-Torreblanca, Edika; Gathergood, John; Loewenstein, George; Stewart, Neil (Review of Economic Studies, 2026)
We study attention utility, the hedonic pleasure or pain derived purely from paying attention to information, which differs from the news utility that arises from gaining new information. The main, field, study examines brokerage account login data to show that investors pay disproportionate attention to already-known positive information on their stocks. Through its effect on logins, this selective attention affects their trading activity. Three experimental studies then show that (1) investors are more likely to engage in a paid task that will involve attention to a prior investment if that investment has gained value; (2) paying attention to a winning stock is more motivating than a doubling of monetary incentives; and that (3) attention has value independent of information acquisition.